2001
DOI: 10.1111/j.1469-0691.2001.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of early diagnosis and aggressive surgery in the management of invasive pulmonary aspergillosis in neutropenic patients

Abstract: Invasive pulmonary aspergillosis (IPA) occurs mostly in immunocompromised hosts and especially in neutropenic patients. Improved prognosis for IPA requires early diagnosis. We report our experience in the management of IPA in patients with hematological malignancies. In prolonged neutropenia (> 10 days), thoracic CT scanning seems to be the best choice for the diagnosis of IPA (with CT halo or air-crescent signs). Its systematic use allows a dramatic reduction in the time to achieve the diagnosis, if there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 46 publications
0
61
2
5
Order By: Relevance
“…A significant bronchospastic component is documented in 79% of patients when reported. As described in the literature [73][74][75][76], fever is present in only 38.5% of patients (15 out of 39), contrasting with the findings in haematological patients where fever is the most common sign (87%) [74]. High-dose corticotherapy could account for the absence of fever.…”
Section: Clinical Features Of Ipa In Copdcontrasting
confidence: 44%
See 2 more Smart Citations
“…A significant bronchospastic component is documented in 79% of patients when reported. As described in the literature [73][74][75][76], fever is present in only 38.5% of patients (15 out of 39), contrasting with the findings in haematological patients where fever is the most common sign (87%) [74]. High-dose corticotherapy could account for the absence of fever.…”
Section: Clinical Features Of Ipa In Copdcontrasting
confidence: 44%
“…However, these results were not confirmed by others [90][91][92], and some authors even reported sensitivity as low as 29.4% [93]. In a multicentre study, sensitivity and specificity were found to be 50 and 97%, respectively, and only one-third of the patients had a positive antigen response before IPA diagnosis on CT scan [74]. Another group reported that although the sensitivity was 82.5% in 40 bone marrow-transplant recipients with proven or probable IPA, the ELISA test was also positive in 31 of 169 patients without any sign of infection [94].…”
Section: Serologymentioning
confidence: 54%
See 1 more Smart Citation
“…The incidence of proven or probable IA in acute leukemia is around 6% but can reach 50% in situations in which there is a risk of Aspergillus propagation and dissemination, such as during building/construction work. [4][5][6][7] Mortality from IA ranges from 40-60% in such patients. 8 Early recognition of IA is an important clinical challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Although these radiological features are characteristic, they are not diagnostic of invasive pulmonary aspergillosis (13,14,15).…”
Section: Discussionmentioning
confidence: 99%